Detection of Crossed Cerebellar Diaschisis by Intravoxel Incoherent Motion MR Imaging in Subacute Ischemic Stroke. Issue 8 (August 2019) - Wang, Juan; Suo, Shiteng; Zu, Jinyan; Zhu, Wanqiu; Pan, Lijun; Song, Shaoli; Li, Yang; Li, Lei; Chen, Zengai; Xu, Jianrong
Intravoxel incoherent motion has received extensive attention in brain studies for its potential as a non-invasive magnetic resonance perfusion method. However, studies on intravoxel incoherent motion imaging and crossed cerebellar diaschisis detection are relatively scarce. The aim of our study was to evaluate the feasibility of using intravoxel incoherent motion imaging in crossed cerebellar diaschisis diagnosis in subacute ischemic stroke patients by comparing results from intravoxel incoherent motion imaging, single-photon emission computed tomography, and arterial spin-labeling perfusion methods. In total, 39 patients with subacute ischemic stroke who underwent intravoxel incoherent motion, arterial spin-labeling, and single-photon emission computed tomography scanning were enrolled. Intravoxel incoherent motion-derived perfusion-related parameters including fast diffusion coefficient, vascular volume fraction, arterial spin-labeling-derived cerebral blood flow as well as single-photon emission computed tomography-derived cerebral blood flow of bilateral cerebellum were measured. A crossed cerebellar diaschisis-positive result was considered present with an asymmetry index ≥10% of single-photon emission computed tomography. In the crossed cerebellar diaschisis-positive group, fast diffusion coefficient, arterial spin-labeling-derived cerebral blood flow, and computed tomography-derived cerebral blood flow of the contralateral cerebellum decreased compared with those of the ipsilesional cerebellum; whereas vascular volume fraction significantly increased. The National Institutes of Health Stroke Scale score and infarct volume in the crossed cerebellar diaschisis-positive group were significantly higher than those in the crossed cerebellar diaschisis-negative group. A positive correlation was detected between the fast diffusion coefficient-based asymmetry index and the single-photon emission computed tomography-based asymmetry index, fast diffusion coefficient-based asymmetry, and arterial spin-labeling based asymmetry index; whereas the vascular volume fraction - based asymmetry index value had a negative correlation with the single-photon emission computed tomography-based asymmetry index and arterial spin-labeling based asymmetry index. Furthermore, the area under the receiver operating characteristic curve value of the arterial spin-labeling-based asymmetry index was 0.923. The fast diffusion coefficient derived from the intravoxel incoherent motion could be valuable for the assessment of crossed cerebellar diaschisis in supratentorial stroke patients.